Pemenuhan Unsur Kepentingan Umum dan Dampaknya Terhadap Hak Masyarakat Dalam Pembangunan Bandara YIA Kulon Progo - Neti Hasiah; Stephanie Tiara Christina; Tsabita Husna Fauziah; Tsabita Zukhrufi Islamiya (UIN Syarif Hidayatullah Jakarta, 2025)
The development of Yogyakarta International Airport (YIA) in Kulon Progo Regency is a National Strategic Project aimed at promoting economic growth and improving the quality of public infrastructure. However, the land acquisition process for this development has triggered significant social conflicts at the local community level. This study analyzes the fulfillment of the public interest criterion in the YIA project, its impact on the protection of the rights of affected communities, and the dynamics of agrarian conflict that emerged, using a socio-legal approach. The findings indicate that although, normatively, the development of YIA complies with the provisions of Law Number 2 of 2012 on Land Acquisition for Development in the Public Interest, its implementation has not fully aligned with the principles of justice, humanity, and participation. The limited involvement of communities in decision-making processes, discrepancies in compensation mechanisms, and the use of consignment as a dispute resolution instrument have contributed to polarization between community groups that support and oppose the project. Agrarian conflicts have been further exacerbated by inconsistencies in spatial planning policies and the loss of residents’ agrarian livelihoods, reflecting unequal power relations between the state and society as explained in Marx’s conflict theory and the concept of agrarian dispossession. This study emphasizes the importance of transparency, fair compensation, and inclusive public participation to ensure that infrastructure development does not generate structural injustice and that its benefits are distributed equitably.